PERANCANGAN DAN IMPLEMENTASI APLIKASI ANDROID UNTUK LAYANAN INFORMASI PARIWISATA - Fransiscus Bryan Prasetio; Theophilus Wellem (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2022)
Android-based applications have been widely used to do daily activities such as online shopping, playing games, video streaming, and watching sports matches. One of the most commonly used applications is applications that assist people for flight or train ticket reservations, hotel bookings, and other recreation purposes. Some tourism companies in Indonesia also develop Android-based applications to provide information and services for their business. Nevertheless, with many tourism destinations in Indonesia, not all tourist attractions have services through Android-based applications published on the Google Play Store. This study aims to design and implement Android-based applications for tourism information services in two tourist attractions as the case study, namely Tay Kak Sie Temple in Semarang City and Beach tourism in Bangka Island, to help tourists obtaining information about both tourist attractions. Both applications are implemented using Compro Mobile App Builder. The testing results using the black box method demonstrate that the implementation of the two applications can run according to the specified specifications.